Pengaruh Suku Bunga Acuan Bank Indonesia, Jumlah Uang Beredar (M2), Dan Inflasi Terhadap Kurs Valuta Asing Tahun 2006-2021 - Shinta Pratiwi; RosyettiAn -; Widayatsari - (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
This study aims to determine the effect of Bank Indonesia's benchmark interest rate, money supply (M2), and inflation on the foreign exchange rate in 2006-2021. The data used in this study is secondary in the form of time series. The analysis method used in this study is a multiple linear regression analysis method with the EViews 12. To find regression results, classical assumption tests were carried out such as normality tests, multicholinearity tests, heteroskedasticity tests, and autocorrelation tests. Statistical tests such as partial tests (t-tests), simultaneous tests (f-tests), and multiple coefficients of determination (R2). The results of this study indicate that the reference interest rate of Bank Indonesia has a significant and positive effect on foreign exchange rates with a value of 557.2729 and a probability value of 0.0020. The money supply (M2) has a significant and positive effect on foreign exchange rates of 1.606582 and the probability value is 0.0000. While inflation has no significant and positive effect on foreign exchange rates of 95.36285 and the probability value is 0.2750. The value of R2 is 0.937854. This means that 93.7854% of the foreign exchange rate variable can be explained by the reference interest rate of Bank Indonesia, the money supply (M2), and inflation. The magnitude of the effect (R2) by the two independent variables as a percentage of the dependent variable is 93.8%. While the remaining 6.2% is influenced by other variables outside of this study.